Checklists of Carp Parasites in Floating Cages of Iraq - Mhaisen, Furhan T. (Iraqi Journal of Aquaculture, 2023)
Literature review of reports concerning the parasitic fauna of floating cage fishes in Iraq till the end of 2021 showed that a total of 57 parasite species are so far known from three fish species investigated for parasitic infections throughout the country. The parasitic fauna included 15 ciliophorans, three myxozoans, two trematodes, 28 monogeneans, five cestodes, one nematode, one acanthocephalan and two crustaceans. The common carp Cyprinus carpio was infected with all these 57 parasite species, the grass carp Ctenopharyngodon idella with four parasite species and the silver carp Hypophthalmichthys molitrix with only one parasite species.